PENINGKATAN KOMPETENSI GURU MTsN KOTA BANDA ACEH MELALUI SUPERVISI PENGAJARAN - Djailani Djailani (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2012)
To achieve vision, mission and the objectives of an institution is determined by capability of the teachers. The development and improvement of teacher must be done systematically, systematic, and be oriented to the four teacher proficiencies. This study aims to determine of how the pattern on increasing the teacher competence in Islamic Junior High School, Banda Aceh, using descriptive methods and the data collection is through observations, interviews and documentation. The subject of the study is head master of the school, chairmen of MGMP, teacher supervisor. The study also uses qualitative analysis. The study shows that: 1) the improvement of the teacher competence at MTsN Banda Aceh has not been supported by realistic program, comprehensive and operational. 2). The implementation of improving the teacher competence is not supported through teacher needs-based program in order to be implemented systematically, well-planned, and sustainably, 3) There is still many internal and external obstacles in implementing the teacher competence through school headmaster supervision and the supervisors could not reach the expected target.